MODAL SOSIAL PEDAGANG KELAPA DI DESA BIDARI TANJUNG DATUK KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Rawi, Zarkani; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted in Bidari Village, Tanjung Datuk, Mandah District, Indragiri Hilir Regency. The problem that is examined is about how social capital among traders occurs in coconut traders in Bidari Tanjung Datuk Village, an analysis of social capital is carried out based on certain propositions. In choosing the subject, the researcher determines the subject based on the author's title, namely coconut traders. For the data collection process, the authors used interview guidelines and conducted in-depth interviews with all research subjects with the aim of obtaining valid data. The results in this study explain that there is a mutually beneficial relationship, which is based on trust in fellow traders. The relationships that were formed made traders mutually beneficial in trade and social life. This is in accordance with the theoretical proposition that the author uses, namely the theory of social capital. After analyzing it, it was found that all the propositions contained in the theory of social capital can be applied in the case of traders who are meticulous researchers. The propositions in question are trust, information networks and norms. Keywords: Traders, Trust, Social capital traders